2021
DOI: 10.1016/j.bbih.2021.100307
|View full text |Cite
|
Sign up to set email alerts
|

Transport study of interleukin-1 inhibitors using a human in vitro model of the blood-brain barrier

Abstract: The proinflammatory cytokine Interleukin-1 (IL-1), with its two isoforms α and β, has important roles in multiple pathogenic processes in the central nervous system. The present study aimed to evaluate and compare the blood-to-brain distribution of anakinra (IL-1 receptor antagonist), bermekimab (IL-1α antagonist) and canakinumab (IL-1β antagonist). A human in vitro model of the blood-brain barrier derived from human umbilical cord blood stem cells was used, where isolated CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
9
0
3
Order By: Relevance
“…Large proteins, like monoclonal antibodies are estimated to enter the brain compartment in a range of 0.1%-1% only. Sjöström et al (2021) recently reported, that Anakinra passes the human brain-like endothelial monolayer at 4.7-fold higher rate than the monoclonal antibodies tested. Therefore, Anakinra may reach the brain compartment at clinically relevant levels, encouraging the utility of Anakinra for treatment of neuroinflammatory diseases.…”
Section: Anakinramentioning
confidence: 92%
“…Large proteins, like monoclonal antibodies are estimated to enter the brain compartment in a range of 0.1%-1% only. Sjöström et al (2021) recently reported, that Anakinra passes the human brain-like endothelial monolayer at 4.7-fold higher rate than the monoclonal antibodies tested. Therefore, Anakinra may reach the brain compartment at clinically relevant levels, encouraging the utility of Anakinra for treatment of neuroinflammatory diseases.…”
Section: Anakinramentioning
confidence: 92%
“…In other diseases, for example, in RA, anakinra is approved to be a relatively safe and modestly efficacious therapy. To be mentioned that existing data suggests that anakinra can cross the blood-brain barrier and reach the brain compartment at clinically relevant concentrations [28].…”
Section: Anti-il-1mentioning
confidence: 99%
“…Canakinumab is a human monoclonal antibody directed against IL-1ß and is amongst others used to treat juvenile idiopathic arthritis [ 195 ] and refractory gout [ 196 ]. The use of canakinumab in AIE may be hampered by its failure to cross the intact BBB [ 197 ]; however, the BBB is likely to become more permissible in AIE and, thus, canakinumab may penetrate the brain parenchyma, as data showing that both canakinumab and anakinra can reach the brain compartment in significant concentration in an in vitro model [ 198 ]. A case report on a patient with generalised epilepsy and poor response to multiple ASMs-reported clinical response after therapeutic IL-1 blockade, first by treatment with anakinra followed by canakinumab with near resolution of seizures [ 199 ].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%